The Correlation Between Widal Diagnostic Test, Total Leukocyte Count, and Platelet Count in Suspected Typhoid Fever Patients at RS Aura Syifa Kediri - Loviana, Novi; Savitri, Lisa; Krissanjaya, Rochmad; Kasimo, Elfred Rinaldo (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2023)
Typhoid fever is an acute systemic infectious disease that is related to poor personal hygiene and environmental sanitation. The diagnosis of typhoid fever is established through laboratory examinations, including serological, hematological, and bacteriological tests. This research aims to determine the correlation between the Widal diagnostic test and the total leukocyte count and platelet count in suspected typhoid fever patients at RS Aura Syifa Kediri. The study design used in this research is quantitative descriptive analysis with a cross-sectional approach. The data was collected retrospectively from secondary sources, specifically medical records of patients from August 1, 2021, to March 31, 2022, at RS Aura Syifa Kediri. The total population comprised 157 patients, and a purposive sampling method was used to select 41 patients who met the inclusion and exclusion criteria. The statistical analysis using the Spearman correlation test resulted in p-values ≥ α = 0.05 for the following correlations: Widal test O with leukocytes (0.538 ≥ 0.05), Widal test H with leukocytes (0.915 ≥ 0.05), Widal test O with platelets (0.476 ≥ 0.05), and Widal test H with platelets (0.965 ≥ 0.05). These findings indicate that there is no significant correlation between the Widal test O and H with the platelet count in patients with typhoid fever. Therefore, it can be concluded that there is no significant relationship between the Widal test O and H results and the platelet count in typhoid fever patients.